Oxford Handbook of Practical Drug Therapy, 1st Edition - Richards, Duncan, Aronson, Jeffrey (OXFORD UNIVERSITY PRESS, 2005)
The overall structure of this handbook is similar to that of the British National Formulary; it is arranged broadly by therapeutic category. When a drug has several different uses, these are brought together in a single article (e.g. lidocaine is used as an antiarrhythmic drug and as a local anaesthetic); this will allow the reader to appreciate its full range of actions, whether therapeutic or adverse. This is not a textbook of pharmacology, but the safe and effective use of medicines requires a sound knowledge of pharmacology. When a drug illustrates a particular pharmacological principle, this is expanded on in the ‘teaching point’ section at the end of an article. As readers use the book, they will increase their basic knowledge in this practical way. A ‘cookbook’ approach to drug therapy is inappropriate, since each prescription constitutes an individual experiment in that patient. However, the text includes boxes giving guidance on the approach to therapy of specific diseases and clinical problems (e.g. the treatment of gout and the symptomatic treatment of vomiting).